Metallogeny of the North Atlantic Craton in Greenland. (2nd January 2018) - Kolb, Jochen; Bagas, Leon; Fiorentini, Marco L.
Abstract: The North Atlantic Craton (NAC) extends along the coasts of southern Greenland. At its northern and southern margins, Archaean rocks are overprinted by Palaeoproterozoic orogeny or overlain by younger rocks. Typical granite-greenstone and granite-gneiss complexes represent the entire Archaean, with a hiatus from ∼3.55–3.20 Ga. In the granulite- and amphibolite-facies terranes, the metallogeny comprises hypozonal orogenic gold and Ni-PGE-Cr-Ti-V in mafic-ultramafic magmatic systems. Gold occurrences are widespread around and south of the capital, Nuuk. Nickel mineralization in the Maniitsoq Ni project is hosted in the Norite belt; Cr and PGE in Qeqertarssuatsiaq, and Ti-V in Sinarsuk in the Fiskenæsset complex. The lower-grade metamorphic Isua greenstone belt hosts the >1000 Mt Isua iron deposit in an Eoarchaean banded iron formation. Major Neoarchaean shear zones host mesozonal orogenic gold mineralization over considerable strike length in South-West Greenland. The current metallogenic model of the NAC is based on low-resolution data and variable geological understanding, and prospecting has been the main exploration method. In order to generate a robust understanding of the metal endowment, it is necessary to apply an integrated and collective approach. The NAC is similar to other well-endowed Archaean terranes but is underexplored, and is therefore likely to host numerous targets for greenfields exploration.